Mechanical properties of filled NR/LLDPE blends - Ahmad A.; Mohd D.H.; Abdullah I. (2023)
Effects of filler (carbon black N110, silica and calcium carbonate) on the mechanical properties of natural rubber (NR) / linear low-density polyethylene (LLDPE) blends have been investigated. The blends were prepared by melt blending in a Haake 6 Rheomix at 140C, 15 min mixing time and a rotor speed of 50 rpm. Fillers were incorporated into the blends for 10-60 vol.%. The mechanical and physical properties of the, blends were found dependent on the filler characterization. Swelling index and elongation-at-break showed a decreasing trend with increasing volume percent of filler loading in the blend. The significant changes in other physical properties included the gel content, and bound rubber of the samples indicated a strong interaction between the filler I particles and polymer matrix. In conclusion, mean agglomerate particles size and polymer-filler interaction are the factors determining the mechanical and physical properties of NR/LLDPE blends.